Kidney transplantation in a patient with preformed and exclusively anti-HLA-Cw donor specific antibody - Santos, S. (2018)
We report a patient who had received a first kidney transplant and had preformed DSA anti-HLA-Cw, developing AMR C4d+ soon after transplant. Classically anti-HLA-Cw are considered less immunogenic and are not considered in many organ allocation systems or immunologic risk stratification algorithms, including in Portugal. However, data from literature confirms that their presence is as deleterious as DSA anti-HLA A/B/DR/DQ. Thus we should take HLA-C typing and respective antibody identification into account in sensitized patients, in order to access risk stratification and establish the need for correct induction or desensitization therapies.